Enforcement of Law Against Perpetrators of Human Trafficking Crimes (Study of Decision Number 432/PID.SUS/2025/PT MDN) - Andalan Cristian Saputra Hia; Yusuf Hanafi Pasaribu; Ramadhany Nasution (SEAN Institute, 2026)
This study examines the enforcement of criminal law against perpetrators of human trafficking, focusing on Decision Number 432/PID.SUS/2025/PT MDN issued by the Medan High Court. Human trafficking cases in Indonesia remain significant due to economic vulnerability and inadequate legal protection for victims. Using qualitative descriptive-analytical methods and library research, this research analyzes the implementation of Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking. The findings reveal that while the court has applied punitive sanctions including imprisonment and fines, victim protection remains insufficient, particularly regarding restitution, identity anonymity, and psychosocial rehabilitation. The study concludes that a more holistic, victim-centered approach is necessary, integrating restorative justice principles and inter-institutional collaboration to ensure comprehensive protection for trafficking victims. The results of the research on Decision Number 432/PID.SUS/2025/PT MDN show that although the Medan High Court has implemented legal protection with criminal sanctions and formal legitimization of victims, the protection is still partial and has not fully adopted the restorative paradigm. There is no direct restitution mechanism, the identity of the victim has not been anonymized, and there is no recommendation for psychosocial rehabilitation. To improve victim protection, it is necessary to integrate restitutive